Geometric Evaluation of Transport Road from P6000BK14 to Disposal at PT. Sinar Nirwana Sari West Kutai East Kalimantan - Abli Febriansyah; Partama Misdiyanta; Mycelia Paradise (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2025)
PT. Sinar Nirwana Sari is a company operating in the coal mining sector with the main activity of transporting materials from the mining front to the disposal area. The condition of the haul road at the research location still shows several discrepancies with road geometry standards, which have the potential to affect the level of productivity and operational safety of hauling equipment. Therefore, this study was conducted with the aim of evaluating the geometry of the haul road based on applicable technical parameters. The method used was the direct measurement method in the field. Data collected were road width, road width on bends, height difference, and bend radius. Furthermore, the data was analyzed with reference to the AASHTO standard. The analysis results showed that the road width on the straight segment had an average value of 16.4 meters, which has met the minimum standard of 15 meters. Meanwhile, the road width on bends had an average value of 20.7 meters, thus meeting the minimum standard of 18.45 meters. The road slope value (grade) was below the maximum limit of 8%, so it was still considered safe. However, the superelevation values, which ranged from 0.8% to 9.2%, indicate that some curves do not meet the recommended 4%. Based on the evaluation results, the average curve width of 20.7 m has met the minimum AASHTO standard of 18.45 m. However, widening is still required on several curve segments that do not meet the minimum standard, while improvements in superelevation are needed on several curves to improve safety and operational efficiency of transportation vehicles.